1997
DOI: 10.1111/j.1365-2222.1997.tb02989.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of allergens from Trisetum paniceum pollen: an important aeroallergen in Mediterranean continental climatic areas

Abstract: Trisetum paniceum pollen contains a high proportion of allergens and these include a group of basic proteins which are not detected in other phylogenetically related pollens and could be of allergological interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…One hundred percent of grass-allergic patients are sensitised to this grass species [6]. T. paniceum pollen has a high proportion of IgE-reactive proteins, including an atypical proportion of basic components which are not detected in other phylogenetically related pollens [7]. The latter study demonstrated cross-reactivity between T. paniceum and other grass pollens, such as Lolium perenne, Festuca elatior, Poa pratensis, Dactylis glomerata, Phleum pratense and Holcus lanatus.…”
Section: Introductionmentioning
confidence: 98%
“…One hundred percent of grass-allergic patients are sensitised to this grass species [6]. T. paniceum pollen has a high proportion of IgE-reactive proteins, including an atypical proportion of basic components which are not detected in other phylogenetically related pollens [7]. The latter study demonstrated cross-reactivity between T. paniceum and other grass pollens, such as Lolium perenne, Festuca elatior, Poa pratensis, Dactylis glomerata, Phleum pratense and Holcus lanatus.…”
Section: Introductionmentioning
confidence: 98%
“…D. glomerata also belongs to the Poaceae family and is widely distributed in Spain and most European countries. While the allergenicity of D. glomerata is well established [24], less is known about the allergenicity of T. paniceum, but it also seems to contain Groups 1 and 5 allergens [25].…”
Section: Introductionmentioning
confidence: 99%
“…Japanese scientists currently use agarose IEF for standard proteomics investigations such as the differential analysis of cancer versus control samples (esophagus 113, liver 114, pancreas 115, 116, colon‐rectum 117, prostate 118), the search for biomarkers (alcoholism 119, X‐ray resistance 120) or the identification of allergens ( Trisetum paniceum pollen 121). However the most specific fields of application of agarose IEF may be in the analysis of high M r components and of membrane proteins.…”
Section: Analysis Of High Molecular Size Proteinsmentioning
confidence: 99%